Investigating the causal association between gut microbiota and type 2 diabetes: a meta-analysis and Mendelian randomization - Liu, Ting; Cao, Yang; Liang, Ning; Ma, Xiaoqi; Fang, Jing-ai; Zhang, Xiaodong (Frontiers in Public Health, 2024)
Background: Studies have shown that gut dysbiosis contributes to the pathophysiology of type 2 diabetes mellitus. Identifying specific gut microbiota dysbiosis may provide insight into the pathogenesis of T2DM.Purpose: This study investigated the causal relationship between gut microbiota and T2DM using meta-analysis and Mendelian randomization (MR).In the first part, we searched for literature on gut microbiota and T2DM, and conducted a meta-analysis. We observed differences in glycosylated hemoglobin and fasting blood glucose levels in both groups. Second, we obtained GWAS data from genome-wide association study database (GWAS). We used two-sample MR analysis to verify the forward and reverse causal associations between gut microbiota and T2DM. Additionally, we selected the European GWAS data from the European Bioinformatics Institute (EBI) as a validation set for external validation of the MR analysis. In the third part, we aimed to clarify which gut microbiota contribute to the degree of causal association between group disorders and T2DM through multivariate MR analysis and Bayesian model averaging (MR-BMA).Results:1. According to the meta-analysis results, the glycated hemoglobin concentration in the gut probiotic intervention group was significantly lower than in the control group.Following treatment, fasting blood glucose levels in the intervention group were significantly lower than those in the control group.2. The results of two samples MR analysis revealed that there were causal relationships between six gut microbiota and T2DM. Genus Haemophilus and order Pasteurellaceae were negatively correlated with T2DM. genus Actinomycetes, class Melanobacteria and genus Lactobacillus were positively correlated. Reverse MR analysis demonstrated that T2DM and gut microbiota did not have any reverse causal relationship. The external validation data set showed a causal relationship between gut microbiota and T2DM.3. Multivariate MR analysis and MR-BMA results showed that the independent genus Haemophilus collection had the largest PP. Conclusion: Our research results suggest that gut microbiota is closely related to T2DM pathogenesis. The results of further MR research and an analysis of the prediction model indicate that a variety of gut microbiota disorders, including genus Haemophilus, are causally related to the development of T2DM. The findings of this study may provide some insight into the diagnosis and treatment of T2DM.